What is a family? : answers from early modern Japan - Berry, Mary Elizabeth, 1947-; Yonemoto, Marcia, 1964- (University of California Press, 2019)
"What Is a Family? explores stories of the Japanese family under the political and social order established by the Tokugawa shogunate (1603-1868). This period showed variation in the ways that families navigated constraints and opportunities. But the circumstances and choices that made one family unlike another were framed, then as now, by the prevailing laws, norms, and controls on resources that shaped all lives. The selected family accounts in this collection of essays focus on a wide variety of individuals ranging from military elite to agrarian villagers and communities of outcastes. Each chapter incorporates diverse sources--from population registers and legal documents to personal letters and diaries--while combining wide accounts of collective practices with intimate portraits of individual actors"--Provided by publisher.